Bioassay of Thuricide, a Microbial Insecticide, against Important forest Pests - Singh, Pratap; Misra, Ram Mohan (Indian Forester, 1978)
Ã—A microbial insecticide thuricide (Potency 30 Ã— 109 spores per gram) with Bacillus thuringiensis as active ingredient was bioassayed against twenty six species of forest Lepidoptera belonging to 11 families.